2020
DOI: 10.1021/acs.joc.0c02459
|View full text |Cite
|
Sign up to set email alerts
|

Anise Essential Oil as a Sustainable Substrate in the Multicomponent Double Povarov Reaction for Julolidine Synthesis

Abstract: The use of star anise oil from a natural source as a dienophile in the multicomponent double Povarov reaction (MCPRs) to produce highly substituted julolidines with diverse technological applications is described. Within the framework of green chemistry, these MCPRs have many advantages such as (i) use of water in the reaction, (ii) creation of up to six bonds in one sequence, (iii) water as a sole waste, (iv) 100% of carbon economy, (v) a metal-free process, and (vi) nontoxic and reusable organocatalysts. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The reaction seems to evolve through a stepwise sequence via ionic intermediates originating oxonium ion 215, which undergoes an intramolecular electrophilic aromatic substitution, under CX4SO3H catalysis, to afford the final products. The same group developed a highly efficient and green synthetic protocol for the preparation of julolidines based on the MCPRs approach, using the same catalyst (CX4SO 3 H) and star anise oil (93% content of trans-anethol) as dienophile (Scheme 51) [139]. A range of substituted anilines 2 reacted smoothly with formaldehyde (195) and trans-anethol (76), in water at 96 • C for 2.5 h, under CX4SO 3 H catalysis giving rise to the diastereoisomeric mixture of julolidines 217 and 218 in yields ranging from 15 to 85%.…”
Section: Catalyzed Diels-alder Cycloaddition Reactionsmentioning
confidence: 99%
“…The reaction seems to evolve through a stepwise sequence via ionic intermediates originating oxonium ion 215, which undergoes an intramolecular electrophilic aromatic substitution, under CX4SO3H catalysis, to afford the final products. The same group developed a highly efficient and green synthetic protocol for the preparation of julolidines based on the MCPRs approach, using the same catalyst (CX4SO 3 H) and star anise oil (93% content of trans-anethol) as dienophile (Scheme 51) [139]. A range of substituted anilines 2 reacted smoothly with formaldehyde (195) and trans-anethol (76), in water at 96 • C for 2.5 h, under CX4SO 3 H catalysis giving rise to the diastereoisomeric mixture of julolidines 217 and 218 in yields ranging from 15 to 85%.…”
Section: Catalyzed Diels-alder Cycloaddition Reactionsmentioning
confidence: 99%
“…In a simple and environmentally friendly methodology, Braga et al 201 reported the synthesis of julolidines 111 and 112 by using star anise oil as a renewable substrate, water as the solvent and CX4SO 3 H as an organocatalyst, obtaining 20 julolidines with yields of 15-87% (Scheme 27). The catalyst was recoverable and reusable for up to four cycles without any significant loss of the catalytic activity.…”
Section: Short Review Synthesismentioning
confidence: 99%
“…In 2020, trans ‐anethole from star anise oil was described as a substrate for julolidine synthesis, using CX34 (4 mol%) in water at 96 °C for 2.5 hours, with yields up to 90 % (Table 25, entry 1) [51c] . Different anilines with electron‐donating and electron‐withdrawing groups were evaluated with yields ranging from 15 % to 90 % (Table 25).…”
Section: Calix[n]arenes As Organocatalystsmentioning
confidence: 99%